Architecture technologique et genèse d’hétérotopies ? - Pascal Krajewski (Appareil)
Architecture, by plugging itself, by covering itself with high tech devices, proposes to us new types of habitats and new ways to inhabit them. The places that are built here are hetero-topias, elsewhere, with which the subject interfaces and into which man transplants himself. So that, perhaps, here, are getting invented the forerunners of technological heterotopias…